The Politics of Marginalization: Assessing the Influence of Inter-Party Marginalization on Women’s Political Empowerment in Balochistan, Pakistan (Journal of Social Sciences Review, 2023)
This research paper delves into the dynamics of marginalization in politics by examining the impact of inter-party marginalization on the political empowerment of women in Balochistan, Pakistan. Given that women make up half of the population, their involvement in various spheres, particularly political development, holds significant importance. The study specifically focuses on women who are active in the political arena, representing eight political parties in Balochistan: ANP, BNP-Mengal, NP, HDP, PkMAP, PML-N, PPPP, and PTI. A sample of 400 respondents was carefully selected from these parties to gather insights into the political participation and empowerment of women in the region. The findings demonstrate a relationship between women's political affiliation with political parties in Balochistan and their marginalization within the realm of party politics. Furthermore, the study highlights the necessity for political parties to provide equal opportunities for women to participate in party politics and emphasizes the importance of fair and unrestricted political engagement. This research sheds light on the level of women's involvement in politics in Balochistan and underscores the potential for further advancements in empowering women through equal representation.
Keywords: Women; Inequality; Politics; Marginalization; Balochistan